Th/Eu abundance ratio of red giants in the Kepler field - Azhari, Ainun; Matsuno, Tadafumi; Aoki, Wako; Ishigaki, Miho N.; Tolstoy, Eline (Astronomy and astrophysics, 2025)
The r-process production in the early Universe has been well constrained by extensive studies of metal-poor stars. However, the r-process enrichment in the metal-rich regime remains poorly understood. In this study, we examine the abundance ratios of Th and Eu, which represent the actinides and lanthanides, respectively, for a sample of metal-rich disk stars. Our sample covers 89 giant stars in the Kepler field with metallicities −0.7 ≤ [Fe/H] ≤ 0.4 and ages ranging from a few hundred million years to approximately 14 Gyr. Age information for this sample is available from stellar seismology, which is essential for studying the radioactive element Th. We derived Th and Eu abundances through χ2 fitting of high-resolution archival spectra (R ≈ 80 000) obtained with the High Dispersion Spectrograph at the Subaru Telescope. We created synthetic spectra for individual stars using a 1D local thermodynamic equilibrium spectral synthesis code, Turbospectrum, adopting MARCS model atmospheres. Our study establishes the use of a less extensively studied Th II line at 5989 Â, carefully taking into account the blends of other spectral lines to derive the Th abundance. We successfully determine the Eu abundance for 89 stars in our sample and the Th abundance for 81 stars. For the remaining eight stars, we estimate the upper limits of the Th abundance. After correcting the Th abundance for decay, we find no correlation between [Th/Eu] and [Fe/H], which indicates that actinide production with respect to lanthanide production does not depend on metallicity. On the other hand, we find a positive correlation of [Th/Eu] with age, with a slope of 0.10 ± 0.04. This may hint at the possibility that the dominant r-process sources are different between the early and late Universe.